Seafloor Pressure Change Excited at the Northwest Corner of the Shikoku Basin by the Formation of the Kuroshio Large-Meander in September 2017 - Nagano, Akira; Yamashita, Yusuke; Ariyoshi, Keisuke; Hasegawa, Takuya; Matsumoto, Hiroyuki; Shinohara, Masanao (Frontiers in Earth Science, 2021)
The Kuroshio takes a greatly southward displaced path called a large-meander (LM) path off the southern coast of Japan on interannual to decadal time scales. The transition of the current path from a non-large-meander path to an LM path is the most salient ocean current variation south of Japan. The change in pressure on the seafloor due to the formation of the LM path in September 2017 is of critical importance to understand the dynamics of the LM path and to distinguish the change due to the Kuroshio path variation from changes due to crustal deformation. Hence, we examined the seafloor pressure across the continental slope off the eastern coast of Kyushu for the period March 2014 to April 2019. The pressure and its cross-slope gradient over the continental slope shallower than 3000 m beneath near the Kuroshio are invariable. As a mesoscale current path disturbance, called a small meander, passed over the observation stations, the pressure decreased by approximately 0.1 dbar on the continental slope deeper than 3000 m and was kept low until the end of the observation period (April 2019). The pressure decrease is consistent with the changes in sea surface height and subsurface water density and is caused by the baroclinic enhancement of the Shikoku Basin local recirculation. This seafloor pressure change implies a strengthening of the deep southwestward current, possibly as a part of a deep cyclonic circulation in the Shikoku Basin. The present study demonstrated that, in addition to altimetric sea surface height data, hydrographic data are useful to distinguish the ocean variation in seafloor pressure from the variation due to crustal deformation, and vice versa.